The Analyzing yield performance of farmers’ and improved varieties of a selected genotype of bread wheat (Triticum aestivum L.) in Goro, Bale, Oromia Region - Jaleta, Benti; Boja, Mesfin (Sustainability Science and Resources, 2024)
The study focused on Analyzing yield performance of farmers’ and improved varieties of a selected genotype of bread wheat (Triticum aestivum L.).The research was conducted in the Bale Zone, Goro Woreda, Oromia Region, Ethiopia.Testing was conducted on sixteen bread wheat varieties, comprising eight farmers' varieties and eight improved variants. During the 2021/22 season, these genotypes were cultivated at the Goro Community Seed Bank using a Randomized Complete Block Design. The analysis of variance revealed significant differences among the genotypes for most traits at the individual level. The majority of traits exhibited a significant (p≤0.05) variety and genotype-by-environment (G×E) interaction. The mean grain yield of the varieties, ranging from 6.67 to 4 tons per hectare, showed considerable variation. Phenotypic coefficient of variation (PCV) exceeded the genotypic coefficient of variation (GCV) for most traits. PCV varied from 2.6% (kernel number per spike) to 36.2% (grain yield), while GCV ranged from 2.23% (kernel number per spike) to 29.9% (grain yield). The heritability estimates for plant height (95.7%) and spike length (91.1%) were both above 80%, indicating a high degree of genetic influence. When considering the percentage of mean, the expected genetic improvement ranged from 0.95% for spike length to 49.14% for grain yield. Positive and negative genotypic and phenotypic relationships were also identified among the yield components. Among the varieties, Tikur Goshmber had the highest grain yield at 33.34kunt/hect, while Tate had the lowest at 11.6 kunt/hect. The improved varieties Kekeba and Digalu had the highest and lowest yields at 39.01 kunt/hect and 10.01 kunt/hect, respectively. It has been observed that the genotypes being studied demonstrate have significant variability, heritability, and correlations among the traits examined that consequently for the advancement of bread wheat yield in the respective area.